Correlation between Awareness of Breast Cancer and Breast Health Awareness among Rural Women: A Cross-Sectional Study - Thi Hang, Nguyen; Van Viet, Tran; Thu Huong, Truong Thi; Thi Hoa, Do; Thanh Tung, Le (Asian Pacific Journal of Cancer Care, 2025)
Introduction: Breast cancer is one of the leading causes of cancer death in women. Breast health awareness through conducting breast self-examination at home, can help women identifying any changes in their breast and thereby it is beneficial for early detection and timely treatment breast cancer. This study aims to identify the correlation between awareness of breast cancer and breast health awareness among women living in rural areas. Materials and methods: A cross-sectional study was conducted on 309 women living in three rural areas in Hai Duong province, Viet Nam by a stratified random sample method. The study questionnaire included awareness of breast cancer, knowledge about breast cancer prevention, and a checklist of women’s breast health awareness. Descriptive statistics and logistic regression were used for data analysis. Results: The study found that most rural women have negative level of breast health awareness (82.5%), and most have low level of knowledge about breast cancer prevention. Perceived benefits of breast health awareness (p<0.001), perceived barriers to breast health awareness (p=0.033), and self-efficacy behind breast health awareness (p=0.001) were factors that affected women’s breast health awareness. Conclusion: The study highlights the need for educational community programs, which should focus on increasing breast cancer awareness and breast health awareness for rural women.